2011
DOI: 10.1103/physreve.84.051907
|View full text |Cite
|
Sign up to set email alerts
|

Entropic attraction of adhesion bonds toward cell boundaries

Abstract: Adhesion bonds between membranes and surfaces are attracted to each other via effective interactions whose origin the entropy loss due to the reduction in the amplitude of the membrane thermal fluctuations in the vicinity of the adhesion bonds. These fluctuation-induced interactions are also expected to drive the adhesion bonds toward the rim of the cell, as well as toward the surfaces of membrane inclusions. In this paper, we analyze the attraction of adhesion bonds to the cell inner and outer boundaries. Our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, the latter depletion-like interactions may play a role in biomembranes and this type of domain formation can be induced not only in adhesion anchor proteins but also in other membrane-associated proteins. It is reported that the adhesion sites are accumulated on fixed membrane boundary [11]. The adhesion sites and other proteins can likely form a domain at a specific region in a plasma membrane via interactions with the cytoskeleton.…”
Section: D Lattice Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the latter depletion-like interactions may play a role in biomembranes and this type of domain formation can be induced not only in adhesion anchor proteins but also in other membrane-associated proteins. It is reported that the adhesion sites are accumulated on fixed membrane boundary [11]. The adhesion sites and other proteins can likely form a domain at a specific region in a plasma membrane via interactions with the cytoskeleton.…”
Section: D Lattice Modelmentioning
confidence: 99%
“…Several groups have been investigated this entropic interaction theoretically [7,[9][10][11][12] and via simulations [8,9]. These studies have reported a weak attraction between adhesion sites, which induces small temporal clusters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is extensive literature on this topic, and the interested reader can consult recent publications [18,19]. Yet another entropic force is proposed to act between surface-membrane bio-adhesion bonds [20].…”
mentioning
confidence: 99%